HYPERTROPHIC CARDIOMYOPATHY IN MULTIMORBIDITY - Lakhonina, A. I.; Filatova, A. V.; Makienko, N. V.; Vodyanitska, N. A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2016)
Aspects of diagnosis, difficulties in the diagnosis and optimal therapeutic strategies in patient with hypertrophic cardiomyopathy and comorbid conditions such as arterial hypertension, ischemic heart disease, dyslipidemia, diabetes mellitus type 2, stenosis of the left renal artery, obesity are reviewed on the example of clinical case. Hypertrophic cardiomyopathy combined with multimorbidity conditions requires a high-quality medical management, where the main goal is to improve the quality and duration of patient's life. This goal is being achieved by optimizing patient's lifestyle and assigning only the minimum amount of medications. Necessity of careful diagnosis of hypertrophic cardiomyopathy, evaluation of the risk of sudden death and search of optimal treatment in patients with multimorbidity pathology are demonstrated in clinical case.